Towards a full automation of land consolidation projects: Fast land partitioning algorithm using the land value map. (September 2022) - Janus, Jarosław; Ertunç, Ela
Abstract: One of the key stages of land consolidation is land reallocation, over the course of which the land of individual owners is pre-allocated to the blocks into which the project area is divided. The key to such an assignment is a set of adopted criteria, the most important of which are the effects of interviewing landowners. The problem of land partitioning is solved either as an optimisation issue in view of the assumed criteria, or as a technical problem related to the automation of the division of a block into new plots with an accuracy sufficient to create the consolidation project documentation and the accuracy requirements of cadastral databases. The article presents an algorithm of an analytical way of dividing a block of any differentiation of the land's value and any shape of the block itself, according to the adopted direction of the course of the new borders. The algorithm may be applied in cases, in which the plot boundaries are parallel to each other and run across the entire block. The speed of the algorithm enables dynamic determination of the plot boundaries in real time. Highlights: Determining plot boundaries is the last technical step in land consolidation. The algorithm of the division of the land block into plots has been presented. The algorithm takes into account a land value map. Plot boundaries are determined without the use of an iterative method.